2011
DOI: 10.1590/s1806-83242011000200011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the accuracy of different transfer impression techniques for multiple implants

Abstract: The aim of this study was to evaluate the accuracy of three implant transfer impression techniques. Four groups (n = 5) were defined, according to the technique: TC -tapered copings without splint; SCsquare copings without splint; SCS -square copings splinted with dental floss and acrylic resin, and CG (control group) -master model with four external hexagonal implants and a superstructure. Individual trays and polyether were used for the impression. All casts were checked for their fit into the master superst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 19 publications
1
39
0
2
Order By: Relevance
“…Ten studies evaluate different coping types . From these, seven studies advocate the open technique with square copings as the most accurate, and three studies report similar results between copings .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies evaluate different coping types . From these, seven studies advocate the open technique with square copings as the most accurate, and three studies report similar results between copings .…”
Section: Resultsmentioning
confidence: 99%
“…5,17,[22][23][24]36 It was verified that a predominant use of square copings was associated to the open technique. Table 2 compares the accuracy between splinted and non-splinted impression techniques, 4,[14][15][16]18,19,[27][28][29]31,37,[39][40][41] resuming the analysis of 14 articles, where all advocate the splinted technique. It was also verified that there was a predominant use of square copings in 10 of the 14 studies.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The open tray technique with the square transfer impressions joined with acrylic resin have been widely used since they were advocated by Branemark 11 . Several authors have studied their effectiveness 8,[11][12] , though the results have not been conclusive in terms of their superiority over other transfer techniques. However, Hsu et al 13 pointed out that "there was no difference in accuracy between moldings carried out using square transfer impressions, whether bonded or not", results which are seen to be in agreement with the findings of Spector et al 11 , Pinto 14 , Goiato et al 15 , Herbest et al 16 and Faria et al 8 , who also found no difference between the two techniques, nor was there any difference when compared with the conical transfer impression technique.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have studied their effectiveness 8,[11][12] , though the results have not been conclusive in terms of their superiority over other transfer techniques. However, Hsu et al 13 pointed out that "there was no difference in accuracy between moldings carried out using square transfer impressions, whether bonded or not", results which are seen to be in agreement with the findings of Spector et al 11 , Pinto 14 , Goiato et al 15 , Herbest et al 16 and Faria et al 8 , who also found no difference between the two techniques, nor was there any difference when compared with the conical transfer impression technique. Burawi et al 5 stated that "the technique that uses transfer impressions that are not bonded is more accurate when compared to the technique that uses bonded transfer impressions, using addition silicone for the molding material".…”
Section: Methodsmentioning
confidence: 99%
“…Já as medidas do grupo teste foram, em média, maiores que 150 µm (tabela 5.10). Caso houvesse sido realizada a união dos transferentes, muito provavelmente melhores resultados teriam sido obtidos, conforme relatado por diversos autores (Assif et al, 1992;Chee;Jivraj, 2006;Cabral;Guedes, 2007;Conrad et al, 2007;Del'Acqua et al, 2008;Filho et al, 2009;Del'Acqua et al, 2010;Yamamoto et al, 2010;Faria et al, 2011 …”
Section: unclassified